2016
DOI: 10.1016/j.tvjl.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria and lipoprotein lipase activity in Miniature Schnauzer dogs with and without hypertriglyceridemia

Abstract: Spontaneous hyperlipidemia in rats causes glomerular disease. Idiopathic hypertriglyceridemia (HTG) is prevalent in Miniature schnauzers, but its relationship with proteinuria is unknown. Decreased activity of major lipid metabolism enzymes, lipoprotein lipase (LPL) and hepatic lipase (HL), may play a role in the cyclic relationship between hyperlipidemia and proteinuria. These enzymes have also not been previously investigated in Miniature shnauzers. The aims of this study were to determine the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 52 publications
1
43
4
Order By: Relevance
“…In people, glomerular lipid thrombi are a hallmark of lipoprotein glomerulopathy, and the disease can progress to nephrotic syndrome if hyperlipidemia is not controlled . However, we found no evidence of nephrotic syndrome in 8 dogs with HTGP, and a previous study similarly reported normal albumin concentrations in 18 dogs with HTGP . Therefore, dogs with HTG, proteinuria, and hypoalbuminemia should not be assumed to have HTGP and should be evaluated for alternative causes of proteinuria.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…In people, glomerular lipid thrombi are a hallmark of lipoprotein glomerulopathy, and the disease can progress to nephrotic syndrome if hyperlipidemia is not controlled . However, we found no evidence of nephrotic syndrome in 8 dogs with HTGP, and a previous study similarly reported normal albumin concentrations in 18 dogs with HTGP . Therefore, dogs with HTG, proteinuria, and hypoalbuminemia should not be assumed to have HTGP and should be evaluated for alternative causes of proteinuria.…”
Section: Discussioncontrasting
confidence: 67%
“…Dogs were included if they were >7 years of age; this cutoff was selected because the manifestations of HTG and proteinuria are age‐dependent . Dogs were not considered for enrollment if they had a history of previously diagnosed diabetes mellitus, hyperadrenocorticism, or hypothyroidism; dogs also were screened for these conditions during the study (see Procedures below).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…25 A recent study documented a strong association between hypertriglyceridemia and proteinuria in Miniature Schnauzers, but the temporal relationship between the 2 abnormalities could be not be determined. 5 …”
mentioning
confidence: 99%